Development and preliminary validation of the visual method ‘3D emotion composition’ for evaluating emotional experience in depression - Inese Paiča; Kristīne Mārtinsone; Māris Taube (Acta Psychologica)
Background: Self-reported measures of emotional experience typically rely on verbal recall, which can be challenging for individuals with depression due to difficulties in emotion differentiation and verbal expression. The 3D Emotion Composition (3DEC) method was developed as a visual, tangible, spatial, and interactive tool to facilitate emotion representation through physical objects. This study aimed to develop and preliminarily validate 3DEC as an alternative method for assessing emotional experience in individuals with depression. Methods: The study was conducted in two phases: (1) development and face validity assessment through expert review and participant feedback, and (2) preliminary validity testing. The 3DEC method was tested for face validity in individuals with and without depression. In the validation phase, 90 participants (45 diagnosed with depression, 45 controls) completed 3DEC and the Emotion Regulation Skills Questionnaire (ERSQ) to assess convergent validity. Known-group validity was examined by comparing 3DEC results between groups. Results: 3DEC showed moderate-to-strong correlations with ERSQ emotion scales (r = 0.30–0.62, p < .001), supporting convergent validity. Known-group comparisons indicated significant differences between patients and controls, with individuals with depression reporting higher sadness, fear, and guilt, and lower joy and interest (p < .001). Conclusions: These findings provide preliminary evidence for the validity of 3DEC as a visual, tangible, and interactive tool for assessing emotional experience in individuals with depression. By capturing aspects of emotional intensity, frequency, and regulation beyond traditional self-report measures, 3DEC may offer valuable insights into emotional processing. Future studies should evaluate its test-retest reliability, sensitivity to therapeutic change, and potential applications in clinical interventions.